An exploration of the experiences and utility of functional electrical stimulation for foot drop in people with multiple sclerosis. Issue 4 (13th February 2020) - (Miller) Renfrew, Linda; Flowers, Paul; Lord, Anna C.; Rafferty, Danny; McFadyen, Angus K.; Bowers, Roy; Mattison, Paul; Paul, Lorna
Abstract: Purpose: Functional electrical stimulation (FES) is effective in improving walking in people with multiple sclerosis (MS) with foot drop. There is limited research exploring people's experiences of using this device. This study aims to explore the utility, efficacy, acceptability, and impact on daily life of the device in people with MS. Methods: An interpretative phenomenological approach was employed. Ten participants who had used FES for 12 months were interviewed. Transcripts were analysed, and emergent themes identified. Results: Nine participants continued to use the device. Three relevant super-ordinate themes were identified; impact of functional electrical stimulation, sticking with functional electrical stimulation, and autonomy and control. Participants reported challenges using the device; however, all reported positive physical and psychological benefits. Intrinsic and external influences such as; access to professional help, the influence of others, an individual's ability to adapt, and experiences using the device, influenced their decisions to continue with the device. A thematic model of these factors was developed. Conclusions: This study has contributed to our understanding of people with MS experiences of using the device and will help inform prescribing decisions and support the continued, appropriate use of FES over the longer term. Implications for Rehabilitation: People with multiple sclerosis using functional electrical stimulation report benefits in many aspects of walking, improved psychological well-being and increased engagement in valued activities. A number of challenges impact on functional electrical stimulation use. Factors such as; a positive experience using the device, access to professional help, the influence of others, a strong sense of personal autonomy and an individual's ability to adapt, influence an individual's decision to continue using functional electrical stimulation. Clinicians prescribing functional electrical stimulation should be aware of these factors so that the right support and guidance can be provided to people with multiple sclerosis, thus improving outcomes and compliance over the long term.